2007
DOI: 10.1051/0004-6361:20077312
|View full text |Cite
|
Sign up to set email alerts
|

Making maps from Planck LFI 30 GHz data

Abstract: This paper is one of a series describing the performance and accuracy of map-making codes as assessed by the Planck CTP working group. We compare the performance of multiple codes written by different groups for making polarized maps from Planck-sized, all-sky cosmic microwave background (CMB) data. Three of the codes are based on a destriping algorithm, whereas the other three are implementations of a maximum-likelihood algorithm. Previous papers in the series described simulations at 100 GHz (Poutanen et al.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 21 publications
0
30
0
Order By: Relevance
“…On the other hand, if the sky signal varies within the pixels, non-uniform sampling of a pixel can cause a systematic error in the solved map (Ashdown et al 2007a). This is an important aspect, as none of the considered algorithms deal with sub pixel structures by design.…”
Section: Direct Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, if the sky signal varies within the pixels, non-uniform sampling of a pixel can cause a systematic error in the solved map (Ashdown et al 2007a). This is an important aspect, as none of the considered algorithms deal with sub pixel structures by design.…”
Section: Direct Methodsmentioning
confidence: 99%
“…(16) to estimate its covariance. The CTP papers (Poutanen et al 2006;Ashdown et al 2007aAshdown et al ,b, 2009 have shown that for Planck the two methods produce maps which are very close to one another. Moreover, they have shown that using a generalized destriper, the derived maps eventually become nearly identical to those obtained with the optimal methods, if an appropriate length of the baseline and a number of the baseline offsets is adopted together with a consistently evaluated prior.…”
Section: Maps and Their Covariancesmentioning
confidence: 97%
See 1 more Smart Citation
“…For Planck's actual scan strategy, scan circle crossings at substantial angles occur over about ±20 • around the poles, so that a much longer run of the circle is involved in constraining the offsets, giving higher signal to noise, and also reducing the sensitivity to monopole-dipole degeneracy. The actual determination of the offsets will be made in the course of iterative destriping, for instance using the madam algorithm (Keihänen et al 2005;Keihänen et al 2010;Ashdown et al 2007;Kurki-Suonio et al 2009). …”
Section: Zero Levels and Destripingmentioning
confidence: 99%
“…3 together with the results of this analysis. The results of the analysis of more realistic Planck data, used in a previous map-making comparison paper (Ashdown et al 2007a), is described in Sect. 4.…”
Section: Introductionmentioning
confidence: 99%